(untitled) (Physical Education, Health and Social Sciences, 2026)
How an international airline can converts constant disruptions into competitive advantage? Prior research on airline resilience studies either hardened contingency systems or passenger’s safety, but rarely integrated these perceptions. This research study employed with a sequential model research design to demonstrate that enduring resilience depends upon the interactions of structural architecture and passenger mind‐sets. We conducted a field study of Pakistan International Airlines’ Emergency Response Centre and frontline operations using survey questionnaire to get information of flows and crisis routines. The study uncovered multiple structural gaps; antiquated playbooks, fragmented real‐time data, ad‐hoc stakeholder shareholder’s communication and weak learning loops that collectively hinder operational recovery. Building on these findings, we deployed a quantitative survey of crisis‐experienced passengers and analyzed the data with partial‐least‐squares modeling. The results revealed that self‐efficacy and self‐control jointly mitigates crisis‐induced distress. However, when self‐efficacy rises beyond a threshold, it can undermine self‐control under acute disruption, indicating that data‐driven reassurance must be paired with behavioral reinforcement rather than stand alone. Together, these insights yields a dual‐path model of aviation resilience, structural redundancy via technology‐enabled contingency planning & psychological redundancy via passenger empowerment. Practically, this study shows how PIA can link AI‐driven disruption dashboards with low‐cost digital “efficacy nudges” (e.g., pre‐flight micro‐briefings and adaptive chatbot coping scripts), delivering rapid resilience gains while longer‐term fleet and systems upgrades proceed. By demonstrating when robust data systems and human judgment reinforce, rather than crowd out each other, the study advances crisis‐management theory and offers an actionable playbook for airlines operating in resource‐constrained, high‐instability environments.